Ketetapan Hukum Bagi Perusahaan Atas Keselamatan Kerja Karyawan Terhadap Kecelakaan Yang Mengakibatkan Korban Jiwa (Studi Kasus Kecelakaan Bus Pariwisata yang Ditumpangi SMK Lingga Kencana Depok) - Afifah, Dashilfa; Aristias, Adinda; Wibowo, Hanifah Fairuz; S, Satino (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Workers are valuable assets for a company that need to be protected through the implementation of Occupational Safety and Health (K3), because threats to their safety and health while working can affect the working relationship between workers and the company, including the risk of traffic accidents. Traffic accidents, which are described in Law no. 22 of 2009 concerning Road Traffic and Transportation, is an unexpected incident involving vehicles and can cause material loss and injury to victims. This research discusses the protection provided by companies for workers who experience accidents, as well as the company’s role in protecting the rights of accident victims as bus passengers. The research method used is the normative juridical method, which examines statutory regulations, legal conceptions, legal principles and legal doctrines related to the problem. The analysis also involved a tourist bus accident case involving passengers from Lingga Kencana Vocational School, Depok. The research results show that the protection provided by the company to workers who experience accidents is very important, where workers have the right to receive compensation for treatment and rehabilitation due to accidents. Apart from that, legal protection for victims of traffic accidents is regulated in Article 240 of the Road Traffic and Transportation Law and Article 191 of the LLAJ Law.